El Síndrome de Burnout en los alumnos en prácticas de fisioterapia (2011)
Physiotherapists are exposed to various occupational stressors, which, if persistent, can lead to the Burnout syndrome, psychosocial phenomenon, consisting of three dimensions: Emotional Exhaustion, Depersonalization and Low Professional Accomplishment. 0bjective: To assess the Burnout syndrome and its association with variables socio-demographic, academic, psychosocial and discomfort/pain.Method: In the search were used MBI-SS (Maslach Burnout Inventory - Student Survey), the scale of Corlet and a questionnaire to identification the demographic variables, academic and psychosocial. The application of instruments was held in places of probation. Results identified average index of Emotional Exhaustion, low Descrença and high rate of effectiveness training, indicating a pre provision for the development of the syndrome. There was also association between the size of Burnout and variable academic, psychosocial and pain, where they had direct relationship with the syndrome. Conclusion: Results point to the need for intervention by the end of current students in order to prevent the Burnout syndrome at work.